2014
DOI: 10.1016/j.ejphar.2014.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia, enhancement of spinal morphine antinociception, and inhibition of tolerance by ultra-low dose of the α2A-adrenoceptor selective antagonist BRL44408

Abstract: Ultra-low doses of non-selective α2-adrenoceptor antagonists augment acute spinal morphine antinociception and block morphine tolerance; however, the receptor involved in mediating these effects is currently unknown. Here, we used tail flick and paw pressure tests on the rat to investigate the acute analgesic and tolerance-inducing effects of spinal morphine and norepinephrine alone or in combination with an ultra-low dose of the α2A-adrenoceptor antagonist, BRL44408. We also assessed the potential antinocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This model, however, does not explain how ultra low doses of α 2A -AR antagonists have the opposite effect on morphine antinociception, i.e. an increase in morphine potency and prolonged antinociceptive effect (Milne et al , 2014). Finally, when measuring the effect of drug interactions at the behavioral level, one cannot exclude the possibility that the interaction involves distinct cells in the system under study.…”
Section: Discussionmentioning
confidence: 99%
“…This model, however, does not explain how ultra low doses of α 2A -AR antagonists have the opposite effect on morphine antinociception, i.e. an increase in morphine potency and prolonged antinociceptive effect (Milne et al , 2014). Finally, when measuring the effect of drug interactions at the behavioral level, one cannot exclude the possibility that the interaction involves distinct cells in the system under study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a series of studies have demonstrated that naloxone, an opioid antagonist, can enhance epinephrine and isoproterenol activity on both cardiac and smooth muscle preparations by mechanisms that do not involve the opioid recep-tor [96][97][98][99][100][101][102]. Similar data demonstrating that β-adrenergic antagonists [52][53][54][55][56][57]103] and α-adrenergic antagonists [50][51][52]58,103] enhance opioid efficacy confirm that the opioid sparing effects and inhibition of tolerance caused by adrenergic drugs and their increase of the duration of opioid analgesia must also be, at least in part, due to direct effects on the opioid receptor rather than through second-messenger mechanisms of cross-talk with adrenergic receptors.…”
Section: Mechanisms Underlying Opioid-adrenergic Enhancementmentioning
confidence: 98%
“…Adrenergic antagonists can also potentiate opioid activity [49]: opioid sparing and decreased tolerance to the opioid has been reported in the presence of prazosin (an α adrenergic antagonist) [50]; ultra-low doses of the non-specific α adrenergic antagonist BRL44408 [51]; phentolamine, an α-blocker, or propranolol, a β-blocker [52]; and the β1specific adrenoceptor blocker, esmolol [53][54][55][56][57]. Idazoxan and other I2-imidazoline ligands that are highly selective α2-adrenoceptor antagonists also attenuated morphine tolerance in rats [58].…”
Section: Introductionmentioning
confidence: 99%
“…A third experiment was conducted in separate groups of animals to assess the effect of coadministration of ULD CB 1 -receptor antagonist RIM (1, 5, 50 ng/kg) with morphine compared with morphine alone (5 mg/kg) or vehicle [5% dimethylsulfoxide (DMSO), 0.3% Tween-80 in 0.9% saline] over 7 days. Our previous studies reported that ULD α 2adrenergic antagonists, atipamezole and efaroxan (Milne et al, 2008(Milne et al, , 2013(Milne et al, , 2014, or CB 1 -antagonist RIM (Paquette et al, 2007) do not alter nociceptive thresholds, and therefore to minimize use of animals, these control groups were not repeated in all experiments.…”
Section: Tolerance Paradigmmentioning
confidence: 99%
“…Recent studies demonstrated that long-term intrathecal administration of an ULD α 2 -adrenergic receptor (AR) antagonist, atipamezole, enhances clonidine analgesia in rats (Milne et al, 2011). In addition, structurally diverse α 2 -AR antagonists, including efaroxan (Milne et al, 2013) and the α 2A -AR subtype selective BRL44408 (Milne et al, 2014), are able to augment spinal morphine analgesia and attenuate development of short-term and long-term opioid tolerance (Milne et al, 2008).…”
Section: Introductionmentioning
confidence: 99%